2016
DOI: 10.1016/j.pcl.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, Bisexual, and Transgender Youth and Family Acceptance

Abstract: Summary In this article, we address theories of attachment and parental acceptance and rejection, and their implications for lesbian, gay, bisexual, and transgender (LGBT) youths’ identity and health. We also provide two clinical cases to illustrate the process of family acceptance of a transgender youth and a gender nonconforming youth who was neither a sexual minority nor transgender. Clinical implications of family acceptance and rejection of LGBT youth are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
116
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(140 citation statements)
references
References 63 publications
2
116
0
7
Order By: Relevance
“…10 -12 Parents' responses to their child's disclosure of their sexual orientation, gender identity, or gender expression (ie, mannerisms, appearance, activity 13 ) can be abusive. 4,9,14,15 For example, a sibling study 16 in which experiences of sexual minority and heterosexual siblings were compared revealed that sexual minority individuals reported more childhood psychological and physical abuse; the findings indicate that sexual minority youth may be "singled out by their parents for maltreatment" (p. 483). 16 Gender nonconforming adolescents also experience higher rates of abuse.…”
mentioning
confidence: 99%
“…10 -12 Parents' responses to their child's disclosure of their sexual orientation, gender identity, or gender expression (ie, mannerisms, appearance, activity 13 ) can be abusive. 4,9,14,15 For example, a sibling study 16 in which experiences of sexual minority and heterosexual siblings were compared revealed that sexual minority individuals reported more childhood psychological and physical abuse; the findings indicate that sexual minority youth may be "singled out by their parents for maltreatment" (p. 483). 16 Gender nonconforming adolescents also experience higher rates of abuse.…”
mentioning
confidence: 99%
“…The scholars Elizur and Mintzer (), Katz‐Wise, Rosario, and Tsappis (), Rosario (), and Zeininger et al () observe that how parents' attitudes toward their lesbian/gay child stabilizes depends on the nature of familial relationships and how the family handles stressful situations involving children. Bowlby's () attachment theory details how coping with child‐related stresses in the family depends on the nature of attachment between the child and their parent(s).…”
Section: Attitudes Stabilizing After Coming Outmentioning
confidence: 99%
“…For example, securely attached parents might become protective of their lesbian/gay child in light of the possible discrimination, victimization, and bullying the child may experience. While being supportive, however, as Katz‐Wise et al () and Zeininger et al () pointed out, they may not always affirm their child's sexuality.…”
Section: Attitudes Stabilizing After Coming Outmentioning
confidence: 99%
See 2 more Smart Citations